2015
DOI: 10.1021/es505142t
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Mats as a Biological Treatment Approach for Saline Wastewaters: The Case of Produced Water from Hydraulic Fracturing

Abstract: Treatment of produced water, i.e. wastewater from hydraulic fracturing, for reuse or final disposal is challenged by both high salinity and the presence of organic compounds. Organic compounds in produced water may foul physical-chemical treatment processes or support microbial corrosion, fouling, and sulfide release. Biological approaches have potential applications in produced water treatment, including reducing fouling of physical-chemical treatment processes and decreasing biological activity during produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…PCR was performed on extracted DNA using the 515F primer and 806R barcoded sequencing primers as previously described (Caporaso et al, 2012; Akyon et al, 2015). After amplification, the PCR products were purified using an Agencourt AMPure Purification Kit (Beckman Coulter, Indianapolis, IN) using a bead ratio of 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed on extracted DNA using the 515F primer and 806R barcoded sequencing primers as previously described (Caporaso et al, 2012; Akyon et al, 2015). After amplification, the PCR products were purified using an Agencourt AMPure Purification Kit (Beckman Coulter, Indianapolis, IN) using a bead ratio of 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…These three pieces of information about a site's native microbes can provide a more thorough explanation of the site microbial ecology. In the past, NGS has been leveraged in water pollution scenarios to explain why microbial mats remove pollutants from wastewater (Akyon et al., ). NGS has also been used to explain why specific bioremediation strategies failed, by tracking microbial function over a specific timescale.…”
Section: Introductionmentioning
confidence: 99%
“…In small-scale tests of hydraulic fracturing fluids and flowback, the effects of salinity on aerobic degradation have been studied- Kekacs et al (2015) found that TDS > 40,000 mg L −1 inhibited biological activity in bottle tests. In small-scale treatability tests, Akyon et al (2015) observed biodegradation of 1.45 mg COD g −1 wet d −1 when TDS = 91,351 mg/L.…”
Section: Figmentioning
confidence: 99%